2021
DOI: 10.1101/2021.06.22.21259273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

More complaints than findings - Long-term pulmonary function in children and adolescents after COVID-19

Abstract: Background: The frequency of persistent symptoms after coronavirus disease 2019 (COVID-19) in adults varies from 4.5% to 87%. Pulmonary function can also show long-term impairment in adults: 10% of hospitalised adults had reduced spirometry values, and 24% had decreased diffusion capacity. To date, only preliminary evidence is available on persistent respiratory sequelae in children and adolescents, therefore our objective was to examine the long-term effects of COVID-19 on pulmonary function in this age group… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…In this study, correlation of clinical symptoms with spirometry showed only mild reduction in FEF25-75z in adults who had reported cough during acute infection. Some previous studies have reported mild reduction of spirometry parameters (20,45) in symptomatic patients, others did not (36,46). All studies show spirometry parameters in the normal ranges-as does the study reported here.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, correlation of clinical symptoms with spirometry showed only mild reduction in FEF25-75z in adults who had reported cough during acute infection. Some previous studies have reported mild reduction of spirometry parameters (20,45) in symptomatic patients, others did not (36,46). All studies show spirometry parameters in the normal ranges-as does the study reported here.…”
Section: Discussionsupporting
confidence: 84%
“…A Swiss study found no changes in spirometry in milder cases 4 months after SARS-CoV-2 infection ( 19 ). Regarding children and adolescents, one study reported no changes in spirometry or CO-diffusion capacity 2 months after SARS-CoV-2 infection in seven children ( 35 ) and one pre-print reports no abnormalities in spirometry or multiple breath washout in 73 children and adolescent 2.6 months after infection ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…The controls were chosen in a very different way among studies, which might have introduced significant heterogeneity. The following were the different definitions of controls: 1) children with other infections (e.g., common cold, pharyngotonsillitis, gastrointestinal, urinary tract infections, pneumonia of bacteria or unknown origin) 16 ; 2) children with no antibodies testing 18 mixed with other children with other infections 16 ; 3) children with a negative antibody test 19 , 4) children with a negative PCR test that were symptomatic 20 ; and 5) children who did not have a positive test recorded in the database 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies adjusted their OR by age, sex, ethnicity, socioeconomic status, and comorbidities 20 . However age and sex 14 only adjusted for sex, only age 16 only adjusted for age, and Knoke et al did not adjust, or by OR without adjusting previous conditions 18 (Supplemental Figures 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…We acknowledge support by the Open Access Publication Funds of the Ruhr-University Bochum. The manuscript was deposited as a preprint in medRxiv with a slightly different title and wording ( 36 ). This work is part of the thesis of Leona Knoke.…”
mentioning
confidence: 99%